Formulation and evaluation of carvedilol melt‑in‑mouth tablet using mucoadhesive polymer and PEG‑6‑stearate as hydrophilic waxy binder - Dangi, Amish Ashvinkumar; Zalodiya, Prakash Bhikhabhai (International Journal of Pharmaceutical Investigation)
Purpose: The demand for melt-in-mouth tablets (MMTs) has been rapidly growing during the last decade, especially for the elderly and children who have swallowing difficulties, to avoid first-pass metabolism and quick drug entry into the systemic circulation. Materials and Methods: In this work, a new approach has been tried to prepare MMTs using a hydrophilic waxy binder [polyethylene glycol (PEG)-6-stearate]. Carvedilol MMTs were prepared by direct compression method using different mucoadhesive polymers such as hydroxypropyl methylcellulose (HPMC), chitosan, and sodium carboxymethyl cellulose (Na-CMC) at various concentrations (range: 0.5–5%) to reduce the flushing action of saliva and to increase mucosal absorption. All the formulations were evaluated for various physiochemical parameters, and the formulations containing the maximum amount of polymer (F4, F7, and F10) were selected for further stability study. Results: The deaggregation time of the tablets was found to be rapid, and the dissolution test revealed that carvedilol was dissolved from the formulation within the compendia limits. This data confirmed that the polymer concentration (0.5–5%) was within acceptable limits. It was also concluded that avicel PH101, pearlitol SD 200, and croscarmellose sodium (CCS) were the appropriate excipients and formulated in the right proportion. Conclusion: As a result, mouth dissolving administration of carvedilol formulated with appropriate excipients and especially with chitosan seems a promising alternative to traditional routes.
Keywords: Carvedilol; croscarmellose sodium; melt‑in‑mouth tablet; pearlitol SD 200